Phase I/II trial of pimasertib plus gemcitabine in patients with metastatic pancreatic cancer. Issue 8 (9th August 2018) - Van Cutsem, Eric; Hidalgo, Manuel; Canon, Jean‐Luc; Macarulla, Teresa; Bazin, Igor; Poddubskaya, Elena; Manojlovic, Nebojsa; Radenkovic, Dejan; Verslype, Chris; Raymond, Eric; Cubillo, Antonio; Schueler, Armin; et al.
Abstract : The selective MEK1/2 inhibitor pimasertib has shown anti‐tumour activity in a pancreatic tumour model. This phase I/II, two‐part trial was conducted in patients with metastatic pancreatic adenocarcinoma (mPaCa) (NCT01016483). In the phase I part, oral pimasertib was given once daily discontinuously (5 days on/2 days off treatment) or twice daily continuously ( n = 53) combined with weekly gemcitabine (1, 000 mg/m 2 ) in 28‐day cycles to identify the recommended phase II dose (RP2D) of pimasertib. In the phase II part, patients were randomised to pimasertib (RP2D) or placebo plus weekly gemcitabine ( n = 88) to investigate progression‐free survival (PFS), overall survival (OS) and safety. The RP2D was determined to be 60 mg BID. PFS and OS outcomes did not indicate any treatment benefit for pimasertib over placebo in combination with gemcitabine (median PFS 3.7 and 2.8 months, respectively, HR = 0.91, 95% CI: 0.58–1.42: median OS 7.3 vs . 7.6 months, respectively). KRAS status did not influence PFS or OS. The incidence of grade ≥3 adverse events was 91.1% and 85.7% for pimasertib/gemcitabine and placebo/gemcitabine respectively, but there was a higher incidence of ocular events with pimasertib/gemcitabine (28.9% vs . 4.8% for placebo/gemcitabine). In conclusion, no clinical benefit was observed with first‐line pimasertib plus gemcitabine compared with gemcitabine alone in patients with mPaCa. Abstract : What's new? Pimasertib is an orally bioavailable small molecule inhibitor of the mitogen‐activated protein kinase kinase 1/2 (MEK1/2) with promise in cancer therapy. Here the authors designed a two‐part clinical trial testing pimasertib combined with the standard of care drug gemcitabine in patients with metastatic pancreatic cancer. No evidence of clinical benefit was observed in the phase II part despite efficacy having been observed in the phase I part, underscoring the need to confirm phase I data in randomized phase II trials.